Thermomechanical Analysis of Various Solid-oxide-fuel-cell Components Using Simple Analog Micrometer Measurements - Malik, Yoga Trianzar; Noviyanti, Atiek Rostika; Lestari, Putri Rizka (Makara Journal of Science, 2020)
The solid oxide fuel cell (SOFC) is a device that can convert the energy stored in gaseous chemicals such as hydrogen into electricity. Because SOFCs are operated at high temperatures, their structures must be stable and durable. The thermomechanical compatibility of SOFC components is the main issue, as negligence in regard to material compatibility leads to cell destruction. In this study, we investigated the thermal expansion coefficient (TEC) of SOFC components, which characterizes their thermomechanical properties. We measured the TEC value of various electrolyte and electrode materials [La9.33Si4O26 (LSO), Ce0.9Gd0.1O1.92 (CGO), La0.8Sr0.2Ga0.8Mg0.2O2.55 (LSGM), LSO-CGO, LSO-LSGM, and La0.7Ca0.3MnO3 (LCM)] using an analog micrometer at temperatures between 298 K and 1073 K. The obtained TEC values matched well with the theoretical references, with errors between 1.80% and 8.00% for LSO, CGO, LSGM, and LCM. The TEC of composite SOFC materials, LSO-LSGM and LSO-CGO, were 10.29 × 10−6 K−1 and 10.10 × 10−6 K−1, respectively. Given the slight difference in their TEC values, these electrolytes would thermomechanically match an LCM cathode.